PENGARUH RASIO LIKUIDITAS DAN LEVERAGE TERHADAP FINANCIAL DISTRESS PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015 – 2017 - Pitri Dwi Prasanti (STIE BIITM, 2019)
The Title Research is The Influence of Liquidity Ratios and Leverage on Financial Distress of Retail Companies Listed on the Indonesia Stock Exchange Period 2015 - 2017. Companies can be categorized as negative financial distress, and companies that merge. To overcome financial problems (financial difficulties) a company can be considered through analysis of financial statements using existing financial ratios. Liquidity ratios and leverage ratios have contributed the most in predicting company bankruptcy. This research aimed to analyze the influence of Liquidity Ratios and Leverage on Financial Distress of Retail Companies Listed on the Indonesia Stock Exchange Period 2015 - 2017. The sample of this research is 15 retail companies listed on the Indonesia Stock Exchange period 2015-2017. The Data sources used in this research are primary and secondary data. Data is analyzed using path analysis that is assisted with SPSS for Windows version 22. Data collection method in this research using document study. The analytical technique used is logistic regression analysis. Results of statistical analysis known that the regression coefficient of the liquidity variable is -0,120 with a significance value of 0.448 so that it shows no significant between the variables of liquidity on financial distress. Regression coefficient leverage variable is -3,296 with a significance value of 0.179 so that it shows no significant effect between the leverage variables on financial distress.